2023
DOI: 10.3390/rs15164101
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Variation in Vegetation Cover and Its Response to Topography in the Selinco Region of the Qinghai-Tibet Plateau

Hongxin Huang,
Guilin Xi,
Fangkun Ji
et al.

Abstract: In recent years, the vegetation cover in the Selinco region of the Qinghai-Tibet Plateau has undergone significant changes due to the influence of global warming and intensified human activity. Consequently, comprehending the distribution and change patterns of vegetation in this area has become a crucial scientific concern. To address this concern, the present study employed MODIS-NDVI and elevation data, integrating methodologies such as trend analysis, Hurst exponent analysis, and sequential cluster analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 69 publications
1
3
0
Order By: Relevance
“…This phenomenon may be due to the fact that with the increase gradually of slope, soil water and nutrients will be more easily lost, so that the percentage of vegetation decline in the higher slope area will be slightly increased ( Zhang et al., 2013 ). Relevant studies show that vegetative coverage in the TPRR is highest at a slope of 35° ( Wang et al., 2021b ), and have concluded that vegetation in this region is less affected by slope ( Huang et al., 2023 ), which is in agreement with the findings of this research.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This phenomenon may be due to the fact that with the increase gradually of slope, soil water and nutrients will be more easily lost, so that the percentage of vegetation decline in the higher slope area will be slightly increased ( Zhang et al., 2013 ). Relevant studies show that vegetative coverage in the TPRR is highest at a slope of 35° ( Wang et al., 2021b ), and have concluded that vegetation in this region is less affected by slope ( Huang et al., 2023 ), which is in agreement with the findings of this research.…”
Section: Discussionsupporting
confidence: 91%
“…Even within the same geographic unit, there are differences in the response of vegetation to climatic factors such as temperature and precipitation ( Deng et al., 2022b ). However, current vegetation monitoring at high altitudes tends to focus on the entire plateau area, using coarse resolution (>500m) AVHRR or MODIS remote sensing imagery to analyze spatial and temporal changes in vegetation ( Zhang and Jin, 2021 ; Han et al., 2023 ; Huang et al., 2023 ). It was shown that the spatial resolution of remote sensing images may affect the accuracy of FVC estimation, and suitable remote sensing images need to be selected according to the study area ( Zhang et al., 2014 ; Wang et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [61] suggested that elevation, slope, and curvature have the greatest influence on the spatial and temporal evolution of vegetation cover in southwest China. Huan et al [62] proposed that the cover of alpine vegetation shows an increasing and then decreasing trend with increasing altitude and slope. The reason for these differences may be that the indicators selected by different studies vary considerably, and this paper considered the influence of detailed landform types more comprehensively than previous scholars who only considered the influence of topographic factors.…”
Section: Geodetector Analysismentioning
confidence: 99%
“…In this study, we used the residual analysis method to separate and quantify the anthropogenic and climatic impacts on NDVI variations at a grid-scale, so as to further identify the main driver of vegetation changes by comparing the residuals between observed NDVI values and predicted NDVI values (Geerken and Ilaiwi, 2004;Sajadi et al, 2021;Lai et al, 2023). We established a multiple regression model between annual NDVI values and corresponding climatic values (precipitation and temperature); the assumption of this model was that the anthropogenic impact on vegetation could be explained by the residual variations derived from the observed values minus the climate-based predicted values (Geerken and Ilaiwi, 2004;Huang et al, 2023). The equations for this calculation are given below.…”
Section: Residual Analysismentioning
confidence: 99%